Eagle syndrome and carotid artery dissection: a rare skull base cause of stroke. Issue 3 (9th March 2022) - Selvadurai, Shaun; Williamson, Andrew; Virk, Jagdeep S; Clarke, Peter
Abstract : Eagle's syndrome is a rare collection of symptoms that occur secondary to an elongated styloid process or calcified stylohyoid ligament irritating its surrounding structures. Classically, this presents as unilateral throat pain or rarely, as acute neurological symptoms secondary to compression of the internal carotid artery: so called 'stylocarotid syndrome'. Significant neurological events in teenagers, secondary to Eagle syndrome have not been reported. We discuss the rare case of a teenage boy, diagnosed with right internal carotid artery dissection and middle cerebral artery infarction, with no cause initially identified. Following further admission with a transient neurological episode, he was noted to have elongated styloid processes with the right abutting the site of carotid dissection. He underwent styloidectomy and has since remained symptom free. This case highlights the importance of considering anatomical variants when assessing young patients with neurological symptoms, and the potential morbidity and mortality benefit that early surgical intervention may have.